2020
DOI: 10.1128/mbio.00849-20
|View full text |Cite
|
Sign up to set email alerts
|

CsrA-Mediated Translational Activation of ymdA Expression in Escherichia coli

Abstract: The sequence-specific RNA-binding protein CsrA is the central component of the conserved global regulatory Csr system. In Escherichia coli, CsrA regulates many cellular processes, including biofilm formation, motility, carbon metabolism, iron homeostasis, and stress responses. Such regulation often involves translational repression by CsrA binding to an mRNA target, thereby inhibiting ribosome binding. While CsrA also extensively activates gene expression, no detailed mechanism for CsrA-mediated translational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Therefore, to determine if Y. pestis rcsB and hfq mRNAs are candidate mRNA targets of CsrA, a position matrix scan ( 44 ) was applied to the 5′ UTR of rcsB and hfq mRNAs to identify putative CsrA binding sites. Up to −250 bases upstream from the translational initiation codon were queried, in keeping with ranges for to-date validated CsrA targeted 5′ UTRs ( 36 , 53 , 54 ). Two potential binding sites were found in the hfq transcript ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to determine if Y. pestis rcsB and hfq mRNAs are candidate mRNA targets of CsrA, a position matrix scan ( 44 ) was applied to the 5′ UTR of rcsB and hfq mRNAs to identify putative CsrA binding sites. Up to −250 bases upstream from the translational initiation codon were queried, in keeping with ranges for to-date validated CsrA targeted 5′ UTRs ( 36 , 53 , 54 ). Two potential binding sites were found in the hfq transcript ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CsrA-dependent biofilm regulation can occur through multiple mechanisms in bacteria. For example, in E. coli , CsrA represses translation of mRNAs encoding DGCs ( 25 ), PgaABCD, a homolog to HmsHFRS ( 36 ), and the NhaR transcriptional regulator that activates pgaABCD transcription ( 70 ) but promotes translation of the ymdA mRNA involved in inhibiting biofilm production ( 54 ). Similarly, we predict that CsrA targets other mRNAs involved in biofilm formation in Y. pestis .…”
Section: Discussionmentioning
confidence: 99%
“…The ymdA gene was identified as the most strongly activated direct mRNA target of CsrA in the E. coli genome in an integrated transcriptomics study (Potts et al, 2017) and may play a role in biofilm formation (Kim and Kim, 2017). Reporter assays and mRNA half-life studies confirmed that CsrA posttranscriptionally activates ymdA expression and stabilizes the ymdA transcript (Renda et al, 2020). In the absence of CsrA, ymdA mRNA forms a hairpin that sequesters the SD sequence, inhibiting ribosome binding.…”
Section: Activation Of Gene Expression By Csra and Orthologsmentioning
confidence: 97%
“…This preference makes CsrA family proteins potent translational repressors whose high-affinity binding can only be overcome by a dedicated protein antagonist, such as FliW or CesT, or a special group of “sponge” RNAs, which will be described in the next section ( Mukherjee et al, 2011 , 2016 ; Altegoer et al, 2016 ; Dugar et al, 2016 ; Katsowich et al, 2017 ; Sowa et al, 2017 ; Ye et al, 2018 ; Oshiro et al, 2019 ). In rare cases, CsrA upregulates the expression of its target through mRNA stabilization or translational activation ( Yakhnin et al, 2013 ; Renda et al, 2020 ).…”
Section: Ontology Of Stable Rnpsmentioning
confidence: 99%